A 5-Ing Sebagai Upaya Pemulihan Kehilangan Pembelajaran pada Peserta Didik MAN 2 Banjarnegara pasca Pembelajaran Jarak Jauh (PJJ) - Ridlo Pramono (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2023)
Due to the Covid-19 pandemic, students have studied from home for nearly two years using the Distance Learning (PJJ) mode. When students start attending school to attend limited face-to-face meetings (PTM), teachers feel that there is a learning loss, thus efforts to restore learning loss are needed. This study discusses how the principal's strategy deals with learning loss problems and recovery strategies that can be implemented after distance learning for students of MAN 2 Banjarnegara. Implementation of the post-PJJ recovery of learning loss program for MAN 2 Banjarnegara students includes: forming a recovery of learning loss work team, coordinating, preparing strategic plans for recovery of learning loss, making the necessary RAB, preparing infrastructure support and infrastructure, involving parents of students , carrying out monitoring, evaluation and follow-up. The strategy applied in the recovery of learning loss program is 5-ing including timing, dressing, behaving, studying and praying. The implementation of the post-PJJ recovery learning loss strategy for students of MAN 2 Banjarnegara went well, as shown by student responses, which stated that 53% of students stated that the implementation of the Post-PJJ Recovery Learning Loss program for students of MAN 2 Banjarnegara had good criteria and 42% of students said it was very good. Based on a questionnaire given to teachers and education staffs, the results obtained were 33% said it was good and 67% said it was very good Abstrak Akibat pandemi covid-19 hampir dua tahun siswa belajar dari rumah dengan mode Pembelajaran Jarak Jauh (PJJ). Manakala siswa mulai masuk sekolah untuk mengikuti pertemuan tatap muka (PTM) terbatas guru merasakan adanya learning loss, dengan demikian perlu upaya pemulihan learning loss. Penelitian ini membahas tentang bagaimana strategi kepala madrasah menangani permasalahan learning loss serta strategi recovery yang dapat dilakukan pasca pembelajaran jarak jauh pada siswa MAN 2 Banjarnegara. Pelaksanaan program recovery of learning loss pasca PJJ pada siswa MAN 2 Banjarnegara meliputi: membentuk tim kerja recovery of learning loss, melakukan koordinasi, menyiapkan rencana starategi recovery of learning loss, membuat RAB yang diperlukan, menyiapkan dukungan asara dan prasarana, melibatkan orang tua peserta didik ,melaksanakan monitoring, evaluasi dan tindak lanjut. Strategi yang diterapkan dalam program recovery of learning loss adalah 5-ing meliputi timing (waktu), dressing (berpenampilan), behaving (bersikap), studying (pembelajaran) dan praying (beribadah). Penerapan strategi recovery of learning loss pasca PJJ pada siswa MAN 2 Banjarnegara berjalan dengan baik ditunjukkan oleh respon siswa yang menyatakan bahwa 53% siswa menyatakan bahwa pelaksanakan program Recovery Learning Loss pasca PJJ bagi siswa MAN 2 Banjarnegara berkriteria baik dan 42% siswa menyakan sangat baik. Berdasarkan angket yang diberikan pada guru dan tenaga kependidikan hasil yang diperoleh senada yaitu 33% menyatakan baik dan 67% menyatakan sangat baik